The meaning of the recovery process and its stages for people attending a mental health day hospital: A qualitative study - Ana Ventosa‐Ruiz; Antonio R. Moreno‐Poyato; Teresa Lluch‐Canut; Isabel Feria‐Raposo; Montserrat Puig‐Llobet (Health Expectations, 2024)
Abstract Introduction This study sought to explore the meaning of the recovery process and its stages from the perspective of people attending a mental health day hospital. Methods A descriptive exploratory qualitative study was carried out. Semi‐structured interviews were conducted with people attending a mental health day hospital. The data were analysed deductively by means of content analysis. Results The participants described the recovery process as a process based on three pillars; the attitude towards recovery, hardship, and the effort required throughout the process. Regarding the stages of recovery, for the participants in the first stage of the process (Moratorium), the search for hope was the most important element. In the second stage (Awareness), the reestablishment of their identity, through the acceptance of the consequences derived from the mental health problem, together with being able to feel full and fulfilled, were the most outstanding elements. In the third stage (Preparation), participants highlighted the search for meaning in life, facing their fears and the process with an open mind. Finally, the last two stages (Rebuilding and Growth) were related to taking responsibility and empowerment for recovery. Conclusions The results of this study provide insight into the perception of the recovery process and its stages in people attending a mental health day hospital. These findings may contribute to aligning the nurse–patient perspective, helping nurses to understand the key elements of patients according to their stage of recovery, and thus be able to subsequently individualise interventions. Patient and Public Contribution This study was based on interviews with 15 patients receiving treatment at an adult mental health day hospital. This study would not have been possible without their participation.